Implementation of integrated disease surveillance and response systems in West Africa: lessons learned and future directions - Stanley Chinedu Eneh; Collins Chibueze Anokwuru; Francisca Ogochukwu Onukansi; Chidera Gabriel Obi; Ogechi Vinaprisca Ikhuoria; Zakariya'u Dauda; Sochima Johnmark Obiekwe; Samson Adiaetok Udoewah (BMJ Health & Care Informatics)
The Integrated Disease Surveillance and Response (IDSR) framework, introduced by the WHO in 1998, aimed to unify disease surveillance across West Africa, replacing fragmented systems. However, challenges such as limited real-time reporting, inadequate data collection and workforce shortages continue to impede disease control and outbreak response. The resurgence of infectious diseases like Ebola, cholera, COVID-19 and monkeypox highlights the need to strengthen IDSR systems for effective public health management. This article reviews IDSR implementation in West Africa, identifying persistent gaps, including delayed outbreak detection, limited laboratory capacity and weak surveillance infrastructure. It emphasises the importance of policy development, capacity building and stakeholder engagement to secure political support and resources. Integrating technological innovations—such as mobile health (mHealth), geographic information systems (GIS), electronic health records and big data analytics—can enhance real-time data sharing and response coordination. Strengthening laboratories, workforce training and monitoring frameworks is essential to improve IDSR performance. Strategic investments are crucial to bolster public health capacities, accelerate response times and mitigate future epidemics in West Africa.